A critical software process selection for very small entities (VSE) - Gledson Hernandes Diniz (2019)
Aligned with the worldwide trend of developing using small teams, most of the critical software has been developed by Very Small Entities (VSE), organizations with up to 25 people. Although there are many process models and standards, the majority of them do not specifically aim the needs of organizations, such as VSE, for whom ISO/IEC 29110 standard was created. The available processes models from ISO/IEC 29110, called Generic Profile Group, are applicable to VSEs that do not develop critical systems or software products. For their use, process models are customized to obtain the project's defined software process, considering individual characteristics. These models, such as the framework from European Space Standardization Coordination (ECSS), generally include provisions for customization based only on the software criticality level, and each organization should eventually select other criteria to indicate the risk that the project is prepared to assume by determining the application of the processes. The set of all possible software is very large, so a set of processes suitable for use by any potential organizations and projects would be excessively general or complex, and difficult to apply. Using standard terminology (documents, processes, activities, tasks, functions, and artifacts) that each organization understands is not a trivial task. Since process selection must be conducted in a thoughtful and disciplined manner, research has been conducted on the effects of project characteristics and their use for project evaluation. Selecting processes requires criteria to assess their relevance to project needs directing to process subsets according to the classification resultant from project evaluation. In this context, the objective of this dissertation is to propose a process selection approach applicable to critical software projects in VSE. Project evaluation is achieved by identifying specific criteria that influence projects and using them in a framework to assess their implications. The projects are classified based on the criticality rating of the software, along with the result of the project evaluation, indicating the use of different process profiles, selected from a common core of international standard requirements. The results show that the selection of project characteristics is a means to support the understanding of influence factors for process selection, and that ECSS processes can be applied to VSE, comprising appropriate process sets according to the evaluation of each project.